Por uma caracterização do turismo em Diamantina: estratégias possíves de interpretação do patrimônio - Erika de Paula Alves (2011)
This thesis aims to understand the development process of the Diamantina´s historic center, recognized by UNESCO as World Heritage, through historical and morphological data. The urban formation underlies discussions raised in this research, that investigates the tourism´s role and possibilities of heritage´s interpretation. It presents analysis considering the Diamantina´s territory appropriation by tourism and its relation with the environment. It is expected that the main contribution of this research is to show urban planning alternatives, that appreciate and value the visitor experience, through the heritage´s interpretation. Simultaneously, contribute to consolidate the city.